2017
DOI: 10.3390/su9101777
|View full text |Cite
|
Sign up to set email alerts
|

Residential Spatial Differentiation Based on Urban Housing Types—An Empirical Study of Xiamen Island, China

Abstract: Abstract:Residential spatial differentiation, also called residential segregation, is a representation of the differentiation of social stratum in economic income, social status, education degree, lifestyle, and other aspects, based on an urban geographical space. In this paper, Xiamen Island is taken as example to calculate the dissimilarity index and the multi-group dissimilarity index at three scales (districts, sub-districts, and communities) by using the land area, population size, and green space area of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Wu et al 2014). More recently, using a case study of Xiamen Island, Sun et al (2017) showed that the smaller the scale of the spatial unit, the larger the spatial differentiation.…”
Section: Socio-spatial Differentiation Segregation and Poverty Concmentioning
confidence: 99%
“…Wu et al 2014). More recently, using a case study of Xiamen Island, Sun et al (2017) showed that the smaller the scale of the spatial unit, the larger the spatial differentiation.…”
Section: Socio-spatial Differentiation Segregation and Poverty Concmentioning
confidence: 99%
“…The poor were the most segregated, according to their higher DI m value. Compared to other studies, Sun et al () found similar DI m values for rich (>0.5) and poor (>0.6) residences in 2014 on Xiamen Island, China. Another study, of Hong Kong, also found that the rich were the most segregated group between 1999 and 2007 (>0.55); however, the poorest households were more evenly distributed (<0.3) (Yip 2012).…”
Section: Resultsmentioning
confidence: 69%
“…Residential characteristics were used to gain insight into the socioeconomic status of the population (Munyati et al ; Yang et al ; Sun et al ). Visual differentiation was based on five spatial residential characteristics (Table ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the studies focused primarily on the suitability of a single type of public facilities, such as education, healthcare, green spaces, etc. [19][20][21][22][23][24][25][26][27][28][29] Composite spatial accessibility assessments for residential suitability have still seldom been published. The reason is that the timeliness and advancement of assessment methods in recent studies, mainly based on traditional social and field surveys, have failed to meet the requirements of contemporary urban studies, which call for full coverage and accurate spatial data for the analysis of larger spatial units and a low updating cost in future studies [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%